2021
DOI: 10.3390/ma14051107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steel Fiber Content on Shear Behavior of Reinforced Expanded-Shale Lightweight Concrete Beams with Stirrups

Abstract: To determine the validity of steel fiber reinforced expanded-shale lightweight concrete (SFRELC) applied in structures, the shear behavior of SFRELC structural components needs to be understood. In this paper, four-point bending tests were carried out on reinforced SFRELC beams with stirrups and a varying volume fraction of steel fiber from 0.4% to 1.6%. The shear cracking force, shear crack width and distribution pattern, mid-span deflection, and failure modes of test beams were recorded. Results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The stirrups can be partially replaced by steel fibres and the combination of steel fibres and stirrups showed a positive effect on the mechanical behaviour of the composite. Similar conclusions have been reached by Ding et al [ 22 ] and Li et al [ 6 ]. Zhao [ 23 ], in his work, additionally characterized the effect of fibres on the reduction of diagonal cracks and strain after cracking.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…The stirrups can be partially replaced by steel fibres and the combination of steel fibres and stirrups showed a positive effect on the mechanical behaviour of the composite. Similar conclusions have been reached by Ding et al [ 22 ] and Li et al [ 6 ]. Zhao [ 23 ], in his work, additionally characterized the effect of fibres on the reduction of diagonal cracks and strain after cracking.…”
Section: Introductionsupporting
confidence: 91%
“…Fibre-reinforced concrete was first used 140 years ago when, in 1874, Bernard submitted his first patent application for steel fibre-reinforced concrete. Since that time, attempts have been made to both evaluate the impact of the fibres on concrete properties [1][2][3][4][5][6][7][8][9], as well as distribution of fibres in the concrete [10][11][12]. Fibre-reinforced concrete has, therefore, become an alternative to ordinary concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Past investigations indicated that lightweight aggregate concrete with more compressive strength could be made; however, the concrete was inclined to brittleness and poor elasticity because an aggregate that is lightweight is typically more brittle in strain (Elongation) [ 13 , 14 ]. The compressive strength capacity of lightweight aggregate concrete is 10 times more than its tensile strength [ 15 , 16 ]. Utilization of peach shells rather than normal crushed aggregates positively affects unit weight, and reduction of unit weight up to 25% might be accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on SFRC have primarily focused on its tensile [ 9 , 20 , 21 , 22 ], shear [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], and flexural behavior [ 5 , 32 , 33 , 34 ]. While, the number of studies on SFRC’s torsional behavior remains limited, although in some load cases the torsional response of beams may govern the overall structural behavior.…”
Section: Introductionmentioning
confidence: 99%